Hubungan Penyakit Infeksi, Pendapatan Keluarga dan Pola Asuh Ibu dengan Status Gizi Balita di Pesisir Pantai Kelurahan Petoaha - Marsud Marsud; Desiderius Bela Dhesa; Siti Hadrayanti Ananda; Ellyani Abadi (Jurnal Kesehatan Masyarakat Celebes, 2022)
Toddler nutritional status is an indicator of Toddler health which is influenced by several factors such as infectious diseases, income and parenting. Nambo Health Center data in 2019 The prevalence of good nutrition is 90.47%, over nutrition is 0.24%, malnutrition is 8.9%, and malnutrition is 0.3%. Increased in 2020 good nutrition 85.49%, over nutrition 0.11%, less nutrition 13.53%, and poor nutrition 0.45%. The purpose of this study was to determine the relationship between infectious diseases, family income and parenting patterns with the nutritional status of children under five. Quantitative research design, cross sectional study approach. The population is all toddlers from fishing families aged 12-59 months in the coastal area of ​​Petoaha, totaling 208 toddlers and a sample of 86 people obtained by purposive side. Data were analyzed using Fisher Exact test. The results showed that the relationship between infectious diseases and eating patterns with nutritional status was obtained with a p value of 0.000 and the relationship between income and nutritional status obtained a p value of 1,000. The conclusion of the study is that there is a relationship between infectious diseases and eating patterns with the nutritional status of children under five and there is no relationship between family income and the nutritional status of children under five on the Coastal Coast of Petoaha Village. Suggestions for the Petoaha Village Government, in order to establish a policy to improve the nutritional status of children under five. For mothers to provide good parenting and for further researchers, to analyze the dominant factors related to the nutritional status of Toddlers in Petoaha Village.